THE EFFECT OF HIGHER ORDER THINKING SKILLS (HOTS) LEARNING MODELS ON THE ABILITY TO WRITE DESCRIPTION THROUGH INTERACTIVE MEDIA IN SD NEGERI 114361 BINANGA DUA LABUHANBATU SELATAN - Rendra Parluhutan Hutapea; Rosmawaty Rosmawaty; Sri Listyarini (Sensei International Journal of Education and Linguistic, 2021)
This type of research is an experiment using pre test and post test control group design. The purpose of this study was to determine the effect of the ability to write descriptions on the Higher Order Thinking Skill (HOTS) Learning Model through interactive media in class VI SD Negeri 114361 Binanga Dua. This research was conducted at SD Negeri 114361 Binaga Dua. Which is located in Binaga Dua District, South Labuhanbatu Regency and its implementation is in the first semester of the 2019/2020 Academic Year. The population in this study were all grade VI students of SD Negeri 114361 Binaga Two academic year 2019/2020, which consisted of 2 classes with a total of 56 students. The sample in this study using purposive sampling. Of the 2 classes that have the same level of mastery, the total sample is selected, where the VIA class is the experimental class with 28 students and the VIB class is the control class with 28 students. Learning Indonesian using the Higher Order Thinking Skills (HOTS) learning model through interactive media can improve the students ability to write descriptions of SD Negeri 114361 Binanga Dua, South Labuhanbatu Regency. There is an average difference in the results of the ability to write descriptions of Indonesian using the HOTS learning model and compared to conventional learning models through interactive media in grade VI SD Negeri 114361 Binanga Dua, South Labuhanbatu Regency It can be concluded that there is an effect of HOTS learning on students' ability to write descriptions through interactive media at SD Negeri 114361 Binanga Dua Labuhanbatu Selatan.